Barriers to consistent and reliable investigation of sudden unexpected infant death: Perspectives from law enforcement. Issue 3 (17th January 2022) - Snippen, Jennifer R.; Cheyney, Melissa; Drake, Stacy A.
Abstract: Despite persistent efforts to advance infant death investigation, most sudden unexpected infant deaths (SUIDs) remain unexplained. Law enforcement officials contribute to SUID investigations throughout the United States, but their impacts on these investigations have not been adequately examined. In this exploratory study, 26 law enforcement officials were interviewed about their experiences and perspectives with SUID investigations. Thematic analysis of qualitative data revealed three specific difficulties law enforcement encounter during SUID investigations: (1) inadequate preparation; (2) overwhelming emotions; and (3) a victim–suspect dilemma. Findings indicate that these barriers may inhibit consistent and reliable investigation of infant death and, therefore, may impede the cause and manner of death determinations. Participants' narratives also offered insights into potential solutions, including expanded SUID training for law enforcement and use of checklists, such as the Sudden Unexpected Infant Death Investigation Reporting Form. The impacts of overwhelming emotions confronted during SUID investigation warrant further study. The victim–suspect dilemma stems from the inability of law enforcement to conclusively eliminate the possibility of homicide. This dilemma may be resolved through a clear distinction between interactions with potential evidence and interactions with the family. Law enforcement must be trained to treat all SUID families in a compassionate and non‐accusatory manner, while investigating all SUID with careful attention to detail that is essential in any potential homicide investigation. A consistent, meticulous, and compassionate approach to SUID investigations will improve the reliability of information obtained and offer the best opportunity for providing answers to grieving parents.